A double‐blind, placebo‐controlled study of adjunctive calcitonin nasal spray in acute refractory mania. (1st April 2013) - Vik, Astrid; Ravindran, Arun; Shiah, I‐Shin; Wong, Hubert; Walji, Nazlin; Lam, Raymond W; Yatham, Lakshmi N
<x xml:space="preserve">Abstract</x> Objectives Calcitonin, a neuropeptide, has been shown in preliminary double‐blind trials to reduce agitation in patients with acute mania. Given that it has effects similar to those of lithium and anticonvulsants on modulation of second‐messenger signaling pathways and stabilization of neuronal membranes, this study examined the efficacy of calcitonin nasal spray in treating acute manic symptoms in patients with treatment‐resistant mania using a double‐blind, placebo‐controlled design. Methods A total of 46 hospitalized patients experiencing either a manic or a mixed episode, who were refractory to treatment with adequate doses of either a mood stabilizer or an antipsychotic, or a mood stabilizer/antipsychotic combination, and had a score of ≥16 on the Young Mania Rating Scale (YMRS), were randomized to receive adjunctive nasal calcitonin 200 IU (n = 24) or saline (n = 22) spray for three weeks. The primary efficacy measure was the change in YMRS scores using the last observation carried forward (LOCF) method. Results The clinical and demographic characteristics were similar between the groups. Patients had a mean YMRS score of 26 in the placebo group and a mean score of 25 in the calcitonin group. There were no significant differences in YMRS scores or percentage responders at three weeks between patients who received calcitonin and those who received placebo. There were also no significant differences in change scores on any other scales. Few patients experienced any adverse events. Conclusions This study does not support the use of nasal calcitonin in the treatment of treatment‐resistant mania.